2017
DOI: 10.1152/ajplung.00271.2016
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to tobacco smoke sex dependently influences methylation and mRNA levels of the Igf axis in lungs of mouse offspring

Abstract: Prenatal exposure to tobacco smoke sex dependently influences methylation and mRNA levels of the Igf axis in lungs of mouse offspring Meyer, Karolin F; Krauss-Etschmann, Susanne; Kooistra, Wierd; Reinders-Luinge, Marjan; Timens, Wim; Kobzik, Lester; Plösch, Torsten; Hylkema, Machteld N Link to publication in University of Groningen/UMCG research database Citation for published version (APA): Meyer, K. F., Krauss-Etschmann, S., Kooistra, W., Reinders-Luinge, M., Timens, W., Kobzik, L., ... Hylkema, M. N. (2017)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 36 publications
3
29
0
Order By: Relevance
“…32 Another study also demonstrated sex-differences, as decreased body weight was observed in female but not male murine offspring after in utero smoke exposure. 33 These studies confirm that the influence of cigarette smoke on fetal growth observed in humans is largely reproducible in mice.…”
Section: Intrauterine Growth Restrictionsupporting
confidence: 70%
See 2 more Smart Citations
“…32 Another study also demonstrated sex-differences, as decreased body weight was observed in female but not male murine offspring after in utero smoke exposure. 33 These studies confirm that the influence of cigarette smoke on fetal growth observed in humans is largely reproducible in mice.…”
Section: Intrauterine Growth Restrictionsupporting
confidence: 70%
“…Smoking either only during the pre‐implantation period, or throughout the entire pregnancy decreased fetal weight significantly, while fetal length was decreased only by exposure in early pregnancy . Another study also demonstrated sex‐differences, as decreased body weight was observed in female but not male murine offspring after in utero smoke exposure . These studies confirm that the influence of cigarette smoke on fetal growth observed in humans is largely reproducible in mice.…”
Section: Models Of Active Cigarette Smoking During Pregnancymentioning
confidence: 62%
See 1 more Smart Citation
“…DNA methylation appears to be dispensable in undifferentiated cells, whereas it is absolutely required in differentiated cells, as genetic deletion of DNA methyltransferase results in embryonic or post-partum lethality [40]. Moreover, DNA methylation plays a pivotal role in regulating gene expression in response to external stimuli, as in the expression of metabolic or developmental genes in the offspring of pregnant mice exposed to different insults [2,41]. Further studies have delineated the biological impact of DNA methylation in cancer by silencing DNA methyltransferases, or by treating cells with DNA demethylating agents [40].…”
Section: Introductionmentioning
confidence: 99%
“…Epigenetic mechanisms, which can be heritable and sensitive to exogenous influence, are independent of the consequences of changes in DNA sequence for regulating gene expression (Feil and Fraga, 2011). Epidemiological and experimental studies have reported an association between prenatal smoke exposure and altered epigenetic methylation patterns in both elementary school-aged children and 30 days post-birth mice (Breton et al, 2009; Meyer et al, 2017). DNA methylation alteration is the process of adding or removing methyl groups to DNA, particularly within gene promoter regions, which can then influence gene regulation, without altering the genetic sequence (Smith and Meissner, 2013).…”
Section: Introductionmentioning
confidence: 99%